High-performance composite thermoelectric thin film and preparation method and application thereof

By mixing Mo2TiC2TX Mxene material with Ag2Te nanowires to prepare high-performance composite thermoelectric films, the problem of low thermoelectric performance of existing thermoelectric devices is solved, and the Seebeck coefficient and power factor is improved, which is suitable for wearable devices.

CN119212537AActive Publication Date: 2024-12-27NANJING UNIV OF POSTS & TELECOMM
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411331121.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2024-12-27
Estimated Expiration
2044-09-24

AI Technical Summary

Technical Problem

The existing thermoelectric devices mainly based on MXene materials have low thermoelectric performance, and the Seebeck coefficient and power factor are insufficient, making it difficult to meet the needs of efficient thermoelectric conversion.

Method used

The Mo2TiC2TX Mxene material was prepared by chemical etching method and mixed with Ag2Te nanowires. The Ag2Te nanowires were synthesized by hydrothermal method, and high-performance composite thermoelectric films were prepared by ultrasonic and vacuum suction layer self-assembly method. The mass of Mo2TiC2TX Mxene material accounts for the total mass 60% of that.

Benefits of technology

It significantly improves the Seebeck coefficient and power factor of the thermoelectric film, optimizes the thermoelectric performance, improves the durability and stability of thermoelectric devices, and is suitable for wearable devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119212537A_ABST
    Figure CN119212537A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of inorganic thermoelectric composite film preparation, and discloses a high-performance composite thermoelectric film and a preparation method and application thereof. The method comprises the following steps: firstly, treating Mo2TiAlC2 by adopting a chemical etching method; then, synthesizing an Ag2Te nanowire by adopting a hydrothermal method; finally, the Ag2Te nanowire solution and the Mo2TiC2TX Mxene material solution are mixed, the mass of the Mo2TiC2TX Mxene material accounts for 60% of the total mass of the Mo2TiC2TX Mxene material and the Ag2Te nanowire, then a vacuum suction filtration layer self-assembly method is adopted, negative pressure generated by a vacuum pump is utilized, solid particles in the mixed solution are intercepted on a filter membrane, the composite thermoelectric thin film is obtained, the thermoelectric performance of the composite thermoelectric thin film is the best, and the composite thermoelectric thin film can be applied to the field of thermoelectric devices. The Seebeck coefficient is obviously improved, and the high thermoelectric performance of the prepared film plays an important role in wearable thermoelectric equipment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of inorganic thermoelectric composite film preparation, and in particular relates to a high-performance composite thermoelectric film and a preparation method and application thereof. Background Art

[0002] Currently, high-performance thermoelectric materials have potential applications in self-powered wearable electronic products. Thermoelectric materials can directly convert thermal energy into electrical energy and have unique advantages. Therefore, people are eager to develop more efficient and flexible thermoelectric materials. MAX compounds can be used to obtain a large number of MXene materials with special properties through chemical etching methods. Due to their mechanical flexibility, they can be used in thermoelectric devices. However, existing thermoelectric devices based on MXene materials show low Seebeck coefficients and power factors, that is, the thermoelectric performance is not high; therefore, there is an urgent need to study thermoelectric films based on MXene materials. Summary of the invention

[0003] The purpose of the present invention is to solve the deficiencies in the prior art and to provide a high-performance composite thermoelectric film and a preparation method and application thereof.

[0004] In order to achieve the above object, the present invention is achieved through the following technical solutions:

[0005] In a first aspect, the present invention provides a method for preparing a high-performance composite thermoelectric film, the method comprising the following steps:

[0006] Step 1, treating Mo2TiAlC2 by a chemical etching method to prepare a Mo2TiC2TX Mxene material solution;

[0007] Step 2, synthesizing Ag2Te nanowires by hydrothermal method;

[0008] Step 3, diluting the Ag2Te nanowires with water to obtain an Ag2Te nanowire solution, then mixing the Ag2Te nanowire solution with a Mo2TiC2TX Mxene material solution, wherein the mass of the Mo2TiC2TX Mxene material accounts for 60% of the total mass of the Mo2TiC2TX Mxene material and the Ag2Te nanowires, then ultrasonicating for 10-30 minutes, and then using a vacuum filtration layer self-assembly method to use the negative pressure generated by a vacuum pump to retain the solid particles in the mixed solution on the filter membrane, and then peeling off from the filter membrane to obtain a composite

[0009] Preferably, the step 1 is specifically:

[0010] First, weigh 30mL of a hydrofluoric acid solution with a solution percentage concentration of 40%, pour it into a polytetrafluoroethylene container, slowly add 1g of Mo2TiAlC2 into the hydrofluoric acid solution in batches, and react in a 55°C oil bath for 72h to obtain a MXene solution; then centrifuge the MXene solution at 5000rpm for 5min, pour out the supernatant, add ultrapure water to dissolve the precipitate, centrifuge and wash, and make the solution pH 7; then add 4mL of TBAOH solution to the solution, and perform ultrasonic treatment for 5min and hand shaking for 20min in turn to obtain a Mo2TiC2TX MXene material solution.

[0011] Preferably, the step 2 is specifically:

[0012] Step 2.1, add 1.44 g of tellurium dioxide, 0.8 g of polyvinyl pyrrolidone, and 1.46 g of sodium hydroxide to 70 mL of ethylene glycol, and stir continuously at room temperature for 6 hours until the solution is clear; then heat the mixed solution at 160° C. for 24 hours and cool to room temperature, then add 70 mL of anhydrous ethanol and stir evenly, then centrifuge at 8500 rpm / min to synthesize tellurium nanowires, and add ethylene glycol to the obtained tellurium nanowires to prepare a 0.01 g / ml tellurium nanowire solution;

[0013] Step 2.2, react 5 g of silver nitrate solid with 50 ml of ethylene glycol, and stir at room temperature for 10 min to prepare a 0.1 g / ml silver nitrate solution;

[0014] Step 2.3, 0.01 g / ml of tellurium nanowire solution and 0.1 g / ml of silver nitrate solution are mixed in a volume ratio of 1:2.5, and then centrifuged and washed with anhydrous ethanol at a speed of 8500 rpm / min to obtain silver telluride nanowires.

[0015] In a second aspect, the present invention provides a high-performance composite thermoelectric film, which is prepared using the preparation method.

[0016] In a third aspect, the present invention provides application of the high-performance composite thermoelectric film in thermoelectric devices.

[0017] The present invention has the following beneficial effects: The present invention proposes to convert Mo2TiC2T X MXene is mixed with Ag2Te nanowires. When Mo2TiC2T X Mxene mass accounts for 2% of Mo2TiC2T X The film with 60% of the total mass of Mo2TiC2T4 nanowires has the best thermoelectric performance and a very significant improvement in the Seebeck coefficient. This is because during the mixing process, Ag2Te4 undergoes phase or structural changes, which optimize its thermoelectric performance. xThe presence of Ag2Te acts as a template or catalyst to promote the formation of a microstructure that is more conducive to thermoelectric conversion. Therefore, this material is expected to promote the development and application of thermoelectric technology. The high thermoelectric performance exhibited by the prepared film plays an important role in wearable thermoelectric devices and ensures the durability and stability of thermoelectric devices.

[0018] In addition, the silver telluride nanowires prepared by the present invention using a tellurium nanowire solution and a silver nitrate solution in a volume ratio of 1:2.5 have the advantages of high aspect ratio, controllable diameter, relatively smooth surface, good mechanical properties, etc., ensuring that the prepared thin film material has beneficial thermoelectric properties, and its preparation process is simple and low cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is a SEM image (10 μm) of silver telluride nanowires with a volume ratio of 1:0.5 between the telluride nanowire solution and the silver nitrate solution;

[0020] Figure 2 This is a SEM image (5 μm) of silver telluride nanowires with a volume ratio of tellurium nanowire solution to silver nitrate solution of 1:0.5;

[0021] Figure 3 This is a SEM image of silver telluride nanowires with a volume ratio of tellurium nanowire solution to silver nitrate solution of 1:1.5 (3 μm);

[0022] Figure 4 SEM image of silver telluride nanowires with a volume ratio of 1:1.5 between telluride nanowire solution and silver nitrate solution (2μm)

[0023] Figure 5 SEM image of silver telluride nanowires with a volume ratio of 1:2.5 between telluride nanowire solution and silver nitrate solution (4 μm)

[0024] Figure 6 SEM image of silver telluride nanowires with a volume ratio of 1:2.5 between telluride nanowire solution and silver nitrate solution (2 μm)

[0025] Figure 7 SEM image of silver telluride nanowires with a volume ratio of 1:2.5 between telluride nanowire solution and silver nitrate solution (1 μm)

[0026] Figure 8 This is the SEM image of Mo2TiAlC2 (4μm);

[0027] Fig. 9 The prepared Mo2TiC2T X SEM image of the cross section of the Mxene material (2 μm);

[0028] Fig.10This is the SEM image (10 μm) of the composite film prepared in Example 1;

[0029] Fig.11 This is the SEM image (20 μm) of the composite film prepared in Example 1;

[0030] Fig.12 XRD pattern of Ag2Te nanowires prepared in Example 1;

[0031] Fig.13 XRD pattern of the composite film prepared in Example 1;

[0032] Fig.14 A physical picture of a composite device prepared from the composite film prepared in Example 1;

[0033] Fig.15 The voltage difference generated by the composite device prepared by the composite film prepared in Example 1 at different temperatures;

[0034] Fig.16 The open circuit voltage of the composite device prepared by the composite film prepared in Example 1 between different temperature gradients;

[0035] Fig.17 The current-voltage curve and output power of the composite device prepared from the composite film prepared in Example 1;

[0036] Fig.18 Comparison of Seebeck coefficients of different composite materials;

[0037] Fig.19 Comparison of power factors of different composite materials;

[0038] Fig. 20 This is a physical picture of the composite material after vacuum filtration. DETAILED DESCRIPTION

[0039] The present invention will be further described below in conjunction with the embodiments, but they are not intended to limit the present invention.

[0040] Study on the Preparation of Ag2Te Nanowires

[0041] First, 1.44 g of tellurium dioxide, 0.8 g of polyvinyl pyrrolidone, and 1.46 g of sodium hydroxide were added to 70 mL of ethylene glycol and stirred at room temperature for 6 hours until the solution was clear. The mixed solution was then added to a 100 mL hydrothermal reactor, heated at 160 ° C for 24 hours, and then cooled to room temperature. 70 mL of anhydrous ethanol was added to the reacted solution and stirred evenly. The synthesized Te nanowires were then centrifuged at 8500 rpm / min, and the Te nanowires were further washed three times with anhydrous ethanol to obtain the tellurium nanowires. Rice noodles are added with ethylene glycol to prepare a 0.01g / ml tellurium nanowire solution; 5g of silver nitrate solid is reacted with 50ml of ethylene glycol, and stirred at room temperature for 10min to prepare a 0.1g / ml silver nitrate solution; finally, the 0.01g / ml tellurium nanowire solution is mixed with the 0.1g / ml silver nitrate solution, and the Ag2Te nanowires are further washed three times by centrifugation at 8500rpm / min with anhydrous ethanol, that is, the silver telluride nanowires are peeled off by a centrifuge-assisted method, and the silver telluride nanowires with a high aspect ratio are obtained. The obtained black solid is dried in an oven at 60°C for 25min, and water is added after drying, and then ultrasonicated for 15min to prepare a silver telluride nanowire aqueous solution and then placed at -20°C for use.

[0042] Different volume ratios of tellurium nanowire solution to silver nitrate solution were studied respectively: (1) The volume ratio of tellurium nanowire solution to silver nitrate solution was 1:0.5, such as Figure 1-2 As shown;

[0043] (2) The volume ratio of tellurium nanowire solution to silver nitrate solution is 1:1.5. Figure 3-4 As shown;

[0044] (3) The volume ratio of tellurium nanowire solution to silver nitrate solution is 1:2.5. Figure 5-7 As shown;

[0045] It can be seen from the attached figure that the silver telluride nanowires prepared by using a tellurium nanowire solution and a silver nitrate solution in a volume ratio of 1:2.5 have the advantages of high aspect ratio, controllable diameter, and relatively smooth surface.

[0046] Example 1

[0047] Preparation of Mo2TiC2T X Mxene material solution:

[0048] The MAX phase (Mo2TiAlC2) was treated by chemical etching. First, 30 mL of a 40% hydrofluoric acid solution was weighed and poured into a polytetrafluoroethylene container. 1 g of the MAX phase material (Mo2TiAlC2) was weighed using an electronic balance and slowly added to the HF solution in batches. The purpose was to prevent the solution from being added too quickly and not being able to dissipate heat in time, thereby causing the solution to splash. HF reacted selectively with the "A" layer (aluminum, Al) in the MAX phase. The reaction formula is as follows: 2Mo2TiAlC2+6HF→2Mo2TiC2+2AlF3+3H2. During this process, , aluminum is replaced by fluoride to generate soluble fluoroaluminate (AlF3), and release hydrogen; after reacting in a 55°C oil bath for 72 hours, a MXene solution is obtained. This time is set to ensure that the "A" layer is completely removed without destroying the layered structure of Mo2TiC2, thereby improving the thermoelectric properties of the prepared film. At this time, the solution is acidic, and the solution is centrifuged at 5000 rpm for 5 minutes. The supernatant is poured out, and ultrapure water is added to dissolve the precipitate. This step is repeated 5 times. At this time, the pH of the solution is close to 7, and a high concentration solution of about 10 mL is obtained. At this time, multi-layer stacked MXenes are obtained. 4 mL of TBAOH solution is added to the solution for intercalation. The multi-layer MXenes (HF etching powder) further react with TBAOH to insert tetrabutylammonium cations (TBA + ), resulting in the shedding of the two-dimensional MXene sheets, and the resulting solution was then treated with ultrasound for 5 min and manual shaking for 20 min to completely detach the nanosheets.

[0049] Preparation of Ag2Te nanowires (tellurium nanowire solution and silver nitrate solution in a volume ratio of 1:2.5):

[0050] First, 1.44 g of tellurium dioxide, 0.8 g of polyvinyl pyrrolidone, and 1.46 g of sodium hydroxide were added to 70 mL of ethylene glycol, and stirred continuously at 25 ° C for 6 hours until the solution was clear; then the mixed solution was added to a 100 mL hydrothermal reactor, heated at 160 ° C for 24 hours and then cooled to 25 ° C, 70 mL of anhydrous ethanol was added to the reacted solution and stirred evenly, and then the synthesized Te nanowires were centrifuged at 8500 rpm / min, and the Te nanowires were further washed three times with anhydrous ethanol. The diol was configured into a 0.01g / ml tellurium nanowire solution; 5g of silver nitrate solid was reacted with 50ml of ethylene glycol, and stirred at room temperature for 10min to prepare a 0.1g / ml silver nitrate solution; finally, the 0.01g / ml tellurium nanowire solution and the 0.1g / ml silver nitrate solution were mixed in a volume ratio of 1:2.5, and the Ag2Te nanowires were further washed three times by centrifugation at a speed of 8500rpm / min with anhydrous ethanol, that is, the silver telluride nanowires were peeled off by a centrifuge-assisted method, and the silver telluride nanowires with a high aspect ratio were obtained. The obtained black solid was dried in an oven at 60°C for 25min, and water was added after drying, and then ultrasonicated for 15min to prepare a silver telluride nanowire aqueous solution and then placed at -20°C for use.

[0051] Preparation of high-performance composite thermoelectric films:

[0052] Mo2TiC2T X The Mxene material solution is mixed with the Ag2Te nanowire solution, wherein Mo2TiC2T X The mass of Mxene material accounts for 2% of Mo2TiC2T X 60% of the total mass of Mxene material and Ag2Te nanowires, then ultrasonic for 10-30 minutes, and then use the vacuum filtration layer self-assembly method to use the negative pressure generated by the vacuum pump (0.098Mpa, flow rate 60L / min) to retain the solid particles or specific components in the mixed solution on the filter membrane, and then peel off from the filter membrane to obtain a composite thermoelectric film. Fig.15 As shown, as time goes by, the greater the temperature difference, the higher the voltage value finally reached, indicating that under a higher temperature difference, the thermoelectric device prepared in this embodiment can generate a better voltage and has better thermoelectric performance; Fig.16 As shown in Figure 2, the output performance at different temperature gradients of 10-60K during this period was studied, indicating that the voltage can be further increased by increasing the temperature gradient to meet actual needs; Fig.17As shown, the voltage and power output curves of the composite material device are shown, which depend on the load current when ΔT is 30K. It can be observed that when the voltage output is 7.1mV and the load current is 89nA, the maximum power density is 0.32μWm-2. At this time, the external resistance is 79kΩ.

[0053] Comparative Example 1

[0054] Compared with Example 1, the difference is:

[0055] Mo2TiC2T X The Mxene material solution is mixed with the Ag2Te nanowire solution, wherein Mo2TiC2T X The mass of Mxene material accounts for 2% of Mo2TiC2T X 20% of the total mass of Mxene material and Ag2Te nanowires, then ultrasonically treated for 10-30 minutes, and then vacuum filtration layer self-assembly method was used to utilize the negative pressure generated by the vacuum pump to retain the solid particles or specific components in the mixed solution on the filter membrane to obtain a composite thermoelectric film.

[0056] Comparative Example 2

[0057] Compared with Example 1, the difference is:

[0058] Mo2TiC2T X The Mxene material solution is mixed with the Ag2Te nanowire solution, wherein Mo2TiC2T X The mass of Mxene material accounts for 2% of Mo2TiC2T X 40% of the total mass of Mxene material and Ag2Te nanowires, then ultrasonically treated for 10-30 minutes, and then the vacuum filtration layer self-assembly method was used to utilize the negative pressure generated by the vacuum pump to retain the solid particles or specific components in the mixed solution on the filter membrane to obtain a composite thermoelectric film.

[0059] Comparative Example 3

[0060] Compared with Example 1, the difference is:

[0061] Mo2TiC2T X The Mxene material solution is mixed with the Ag2Te nanowire solution, wherein Mo2TiC2T X The mass of Mxene material accounts for 2% of Mo2TiC2T X 80% of the total mass of Mxene material and Ag2Te nanowires, then ultrasonically treated for 10-30 minutes, and then vacuum filtration layer self-assembly method was used to utilize the negative pressure generated by the vacuum pump to retain the solid particles or specific components in the mixed solution on the filter membrane to obtain a composite thermoelectric film.

[0062] Comparative Example 4

[0063] Compared with Example 1, the difference is:

[0064] Mo2TiC2T X The Mxene material solution adopts the vacuum filtration layer self-assembly method to utilize the negative pressure generated by the vacuum pump to retain the solid particles or specific components in the mixed solution on the filter membrane to obtain a composite thermoelectric film.

[0065] A mechanically supported film was obtained by vacuum filtration layer self-assembly method. Fig.18 and Fig.19 From the above, when Mxene accounts for 60% of the total, it shows a high Seebeck coefficient and power factor, that is, the thermoelectric coefficient is optimal, and has better thermoelectric performance. Further increasing the proportion of Mxene will lead to a decrease in the thermoelectric coefficient.

[0066] Preparation of composite devices:

[0067] like Fig.14 As shown, the composite film prepared in Example 1 is cut into 6 groups of long strips of uniform size and shape, and the device is packaged as a whole. The flexibility of the device enables it to adapt to the curved structure of the human body and still maintain good contact and performance in a bent state.

[0068] The above shows and describes the basic principles, main features and advantages of the present invention. However, the above is only a specific embodiment of the present invention, and the technical features of the present invention are not limited thereto. Any other implementation methods derived by any technician in the field without departing from the technical solution of the present invention should be included in the patent scope of the present invention.

Claims

1. A method for preparing a high-performance composite thermoelectric film, characterized in that: The method comprises the following steps: Step 1: Mo2TiAlC2 is treated by chemical etching to obtain Mo2TiC2T X Mxene material solution; Step 2, synthesizing Ag2Te nanowires by hydrothermal method; Step 3: dilute the Ag2Te nanowires with water to obtain an Ag2Te nanowire solution, and then mix the Ag2Te nanowire solution with Mo2TiC2T X Mxene material solution is mixed, wherein Mo2TiC2T X The mass of Mxene material accounts for Mo2TiC2T X 60% of the total mass of Mxene material and Ag2Te nanowires, then ultrasonically treated for 10-30 minutes, and then the vacuum filtration layer self-assembly method was used to utilize the negative pressure generated by the vacuum pump to retain the solid particles in the mixed solution on the filter membrane, and then peeled off from the filter membrane to obtain a composite thermoelectric film.

2. The method for preparing a high-performance composite thermoelectric film according to claim 1, characterized in that: The step 1 is specifically as follows: First, weigh 30 mL of a hydrofluoric acid solution with a concentration of 40% and pour it into a polytetrafluoroethylene container. Then, slowly add 1 g of Mo2TiAlC2 into the hydrofluoric acid solution in batches. After reacting in an oil bath at 55 °C for 72 h, a MXene solution is obtained. Then, the MXene solution is centrifuged at 5000 rpm for 5 min, the supernatant is poured out, ultrapure water is added to dissolve the precipitate, and the solution is centrifuged and washed to a pH of 7. Then, 4 mL of TBAOH solution is added to the solution, and ultrasonic waves are performed for 5 min and hand shaking for 20 min in turn to obtain Mo2TiC2T X Mxene material solution.

3. The method for preparing a high-performance composite thermoelectric film according to claim 1, characterized in that: The step 2 is specifically as follows: Step 2.1, add 1.44 g of tellurium dioxide, 0.8 g of polyvinyl pyrrolidone, and 1.46 g of sodium hydroxide to 70 mL of ethylene glycol, and stir continuously at room temperature for 6 hours until the solution is clear; then heat the mixed solution at 160° C. for 24 hours and cool to room temperature, then add 70 mL of anhydrous ethanol and stir evenly, then centrifuge at 8500 rpm / min to synthesize tellurium nanowires, and add ethylene glycol to the obtained tellurium nanowires to prepare a 0.01 g / ml tellurium nanowire solution; Step 2.2, react 5 g of silver nitrate solid with 50 ml of ethylene glycol, and stir at room temperature for 10 min to prepare a 0.1 g / ml silver nitrate solution; Step 2.3, 0.01 g / ml of tellurium nanowire solution and 0.1 g / ml of silver nitrate solution are mixed in a volume ratio of 1:2.5, and then centrifuged and washed with anhydrous ethanol at a speed of 8500 rpm / min to obtain silver telluride nanowires.

4. A high-performance composite thermoelectric film, characterized in that: The film is prepared by the preparation method according to any one of claims 1 to 3.

5. Application of the high-performance composite thermoelectric film according to claim 4 in thermoelectric devices.

Citation Information

Patent Citations

  • Preparation method and application of MXene nano-sheet with Mo vacancy

    CN108383121A

  • Preparation method of polyvinylpyrrolidone / silver / silver telluride ternary flexible composite thermoelectric film

    CN110061121A

  • Silver telluride nanowire flexible thermoelectric film welded at room temperature and preparation method therefor

    WO2021016876A1

  • Materials and methods of use thereof

    WO2024076558A1